(untitled) (Research, Society and Development, 2024)
This study addresses the effectiveness of memory regression as a therapeutic method for individuals with blood-injection-injury (BII) phobia, a condition that manifests itself through extreme fear and avoidance of seeing blood, receiving injections, or being present in invasive medical situations. Differentiated from other phobias by its unique physiological response, including fainting, and the feeling of disgust, BII significantly impacts patients’ lives, limiting access to essential medical care and influencing professional and lifestyle choices. The prevalence of this phobia ranges from 0.8 to 1.5% among children and adolescents, reaching 3 to 4.5% in adults, but its therapeutic approach is often neglected in the specialized literature. This article explores memory regression as a promising intervention, suggesting that by revisiting and reinterpreting the past traumatic experiences that underlie the phobia, patients can achieve a deeper understanding and resolution of their fears. Preliminary results indicate a significant reduction in anxiety and phobic avoidance, demonstrating the potential of memory regression as a valuable tool in the therapeutic arsenal for the treatment of IBD. This study contributes to the field of psychotherapy by providing insights into the applicability and efficacy of memory regression, emphasizing the importance of innovative approaches in the treatment of specific phobias.